Multiple Trichofolliculomas in An Adolescent Female: A Case Report (Journal of Science and Technology, 2024)
Trichofolliculoma is a rare benign tumour of hair follicle tissue that is often found on the face and neck. It is usually a dome-shaped papule or nodule with a central pore and a tuft of immature hairs growing through it. It typically presents as a solitary lesion, with onset in adulthood.  We report a rare case of multiple facial trichofolliculomas in an adolescent female, with onset in childhood. The patient was a 12-year-old who presented with non-pruritic facial lesions of seven years duration that were occasionally painful. On examination, multiple skin-coloured nodules and papules with central pores confined to the face were noted. The lesions were numerous, hence presenting a challenge in individually counting them. Nevertheless, we estimated the number of lesions to exceed 120. There was no hair, nails, mucosae, or systemic involvement.  The clinical diagnosis of trichofolliculoma was confirmed with an excision biopsy of a single lesion for histopathology. Treatment was with curettage under local anaesthesia for cosmetic reasons. Healing was rapid (within four to five days) with no significant scarring or recurrence after six months of follow-up. Multiple trichofolliculomas, though uncommon, can manifest in young patients. Histological diagnosis is critical in treatment because it helps to rule out similar conditions.